Necessity of Temporal Artery Biopsy for Giant Cell Arteritis: A Systematic Review. Issue 5 (20th May 2022) - Ponich, Brett; Hartley, Rebecca; Lafreniere, Ann-Sophie; Temple-Oberle, Claire F.
Abstract : Background: Temporal artery biopsy (TAB) is currently the gold standard procedure to diagnose giant cell arteritis. Despite low sensitivity, TAB is routinely performed even if a clinical diagnosis has already been made. The objective of this study was to determine the usefulness of TAB for giant cell arteritis management. Methods: We performed a systematic review to identify studies that compared steroid treatment between TAB+ and TAB− patients. EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials were searched from inception until April 4, 2020. Titles, abstracts, and full texts were reviewed by two independent reviewers and conflicts resolved by consensus. Studies reporting TAB result and steroid treatment were included. Information pertaining to steroid treatment was compared between TAB+ and TAB− groups. Steroid duration was compared by grouping patients in a less than 6 month group, a 6–24 month group, and a more than 24 month group. Results: An estimated 5288 abstracts were screened and 13 studies involving 1355 patients were included. Rate of prebiopsy steroid treatment was higher in TAB+ patients compared with TAB− patients [93% versus 63% ( P < 0.001)]. The TAB+ group was more likely to be started on steroids prebiopsy [28% versus 8% ( P < 0.001)]. TAB+ and TAB− patients had similar steroid duration for all groups [<6-month group 17% versus 19% ( P -0.596), the 6-24-month group 16% versus 19% ( P -0.596), and the >24-month group 66% versus 63% ( P -0.642)]. Conclusion: TAB results have minimal impact on treatment, and the utility should be reconsidered when a clinical diagnosis of giant cell arteritis is possible.